2021
DOI: 10.1016/j.jhep.2020.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on global HCV elimination efforts

Abstract: With only 10 years left to meet the WHO's hepatitis elimination targets, COVID-19 is impacting progress. A 1-year delay in HCV programs could cause excess HCV morbidity and mortality. A 1-year delay could cause 72,000 excess deaths from HCV. Most excess deaths would be in the lower middle income and highincome groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
221
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(248 citation statements)
references
References 4 publications
6
221
0
7
Order By: Relevance
“…An additional concern is how exposure to COVID-19 among people who use drugs exacerbates co-occurring invasive bacterial infections, particularly community-acquired pneumonia and infective endocarditis ( Jacka, et al, 2020 ). We note the need to better understand, as well as address, how COVID-19 entangles with other viral infections, especially HIV ( Golin et al, 2020 , Vasylyeva et al, 2020 , Wilkinson and Grimsrud, 2020 ) and HCV ( Blach et al, 2020 , Karimi-Sari and Rezaee-Zavareh, 2020 ). A concern here is how COVID-19 responses stretch the already limited resources available in some settings to maintain the scale-up of prevention and treatment required across multiple viral infections affecting people who use drugs, risking the disruption or slowing of progress towards achieving viral elimination targets in relation to HIV ( Golin et al, 2020 , Wilkinson and Grimsrud, 2020 ) and HCV ( Blach et al, 2020 , Karimi-Sari and Rezaee-Zavareh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…An additional concern is how exposure to COVID-19 among people who use drugs exacerbates co-occurring invasive bacterial infections, particularly community-acquired pneumonia and infective endocarditis ( Jacka, et al, 2020 ). We note the need to better understand, as well as address, how COVID-19 entangles with other viral infections, especially HIV ( Golin et al, 2020 , Vasylyeva et al, 2020 , Wilkinson and Grimsrud, 2020 ) and HCV ( Blach et al, 2020 , Karimi-Sari and Rezaee-Zavareh, 2020 ). A concern here is how COVID-19 responses stretch the already limited resources available in some settings to maintain the scale-up of prevention and treatment required across multiple viral infections affecting people who use drugs, risking the disruption or slowing of progress towards achieving viral elimination targets in relation to HIV ( Golin et al, 2020 , Wilkinson and Grimsrud, 2020 ) and HCV ( Blach et al, 2020 , Karimi-Sari and Rezaee-Zavareh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the first wave of the COVID-19 pandemic produced an unexpected overwhelm of health systems, whose consequences were not those virus-related only, but also the drop in the diagnosis of other diseases [4]. Along this line, Blach et al [5] modeled brightly the devastating consequences of delaying HCV elimination programs. This delay will be reflected in an increase of HCV-related mortality, both as consequence of cirrhosis complications and hepatocellular carcinoma (HCC) development.…”
Section: To the Editormentioning
confidence: 99%
“…In fact, a recent survey evaluating the collateral damages of COVID19 on VH services showed that up to 64% of participants reported the impossibility to access to viral testing, with the closure of testing facilities being its main cause in the United States [7]. Consequently, this diagnosis adjournment J o u r n a l P r e -p r o o f will be translated into a patent delay in starting DAA, whose future consequences have just been predicted by Blach et al [5], which we already knew from the past [8].…”
Section: To the Editormentioning
confidence: 99%
“…The pandemic has had an impact on all stages of the HCV care cascade and has reduced access to essential medical services among priority populations (ie, people disproportionately affected by HCV), including people who use drugs (4). Although governments are rightfully focused on controlling transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), marginalized populations struggle to maintain access to harm reduction and drug treatment services (5)(6)(7)(8).…”
Section: To the Editormentioning
confidence: 99%